(untitled) (Bangladesh Critical Care Journal, 2022)
Background: Intensive care unit (ICU) is the backbone of critical care service delivery in a hospital. Bangladesh has been lagging behind in critical care service delivery since first ICU was established in 1978. In 2017-19 an international study reported that Bangladesh had 0.7 Critical care (ICU and HDU) bed per one lac population. This was quite low compared to South Asian countries. Growth of critical care beds across our country has been reported to be heterogeneous. The aim of this survey is to determine current strength and growth of critical care beds before the beginning of recent COVID pandemic and also at the height of pandemic when additional COVID ICUs and HDUs were introduced. Method: Data on number of ICUs and HDUs and their bed strength were obtained from different web sites of Govt. of Bangladesh as well through personal communication. Number of critical care beds were calculated at national and district level as number per one lac population. Ratio of critical care beds expressed in percentage with number of hospital beds in the hospital were calculated at national level. Data were also obtained on COVID ICU and HDU beds which were introduced temporarily from websites of ministry of Health, Govt. of Bangladesh. Results: As of now we documented (pre COVID pandemic) 2139 ICU beds (965 in Govt. hospitals) and 717 HDU beds (315 in Govt. hospitals) among 208 hospitals (Govt. hospitals 79+ Private hospitals 129) during our survey. Number of critical care beds per one lac population across the country is found to be 1.70. In hospitals with critical care beds the average ratio of critical care beds (ICU+HDU) beds compared to hospital beds is 4.34% across the country. Thirty eight of total 64 districts have no critical care facility (non COVID/pre COVID) in their local hospitals. During peak of pandemic Govt. of Bangladesh introduced and approved 1186 COVID ICU beds, 695 COVID HDU beds both at Govt. and private level on temporary basis in different hospitals including in some critical care deprived hospitals. Conclusion: Our survey concludes that growth and distribution of critical care beds (ICUS + HDUs) across Bangladesh is still heterogeneous and very much inadequate compared to the critical care need of the population. There was a temporary surge of new ICUs and HDUs to serve COVID patients at the height of COVID pandemic across the country. Health care planners of the country need to plan for developing adequate critical care man power as well as establish newer critical care facilities among existing hospitals who lack them. Bangladesh Crit Care J September 2022; 10(2): 88-98